2012
DOI: 10.1007/s10552-012-9907-z
|View full text |Cite
|
Sign up to set email alerts
|

Exposure to second-hand smoke at home and its associated factors: findings from the Global Adult Tobacco Use survey in Vietnam, 2010

Abstract: The study showed that a high percentage of people are exposed to second-hand smoke at home. Disadvantaged people were more likely than the better-off to be exposed to SHS at home.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

1
6
0

Year Published

2012
2012
2018
2018

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 9 publications
(7 citation statements)
references
References 14 publications
(15 reference statements)
1
6
0
Order By: Relevance
“…Consistent with a survey in Vietnam (8), women and younger adults are more likely to be exposed at home. Overall, however, SHS exposure at home may be higher in Vietnam than among Vietnamese in California (8), possibly because of California’s history of implementing stringent tobacco control strategies (9) or acculturation stemming from these policies. Eight percent of employed men had SHS exposure at work.…”
Section: Discussionsupporting
confidence: 77%
“…Consistent with a survey in Vietnam (8), women and younger adults are more likely to be exposed at home. Overall, however, SHS exposure at home may be higher in Vietnam than among Vietnamese in California (8), possibly because of California’s history of implementing stringent tobacco control strategies (9) or acculturation stemming from these policies. Eight percent of employed men had SHS exposure at work.…”
Section: Discussionsupporting
confidence: 77%
“…For example, in Vietnam, smoking among men is socially acceptable; SHS exposure among pregnant women is widespread. [ 21 ] Similarly, in Bangladesh, [ 22 ] 46.7% of reproductive-aged women reported exposure to SHS at home. One study applying HBM to help nonsmoking pregnant women to avoid SHS in China; the results were not very encouraging as most pregnant women felt powerless and lacked self-efficacy to stop smokers around them from smoking.…”
Section: Discussionmentioning
confidence: 99%
“…This review summarized information available to date and revealed some areas in need of further investigation. The review is useful for providing suggestions about the content of future intervention studies; the findings may be relevant for other Southeast and Southwest Asian countries such as Vietnam ( 30 ) and Bangladesh. The situation in Vietnam is similar to that in China: smoking among men is socially acceptable, and there is considerable SHS exposure among pregnant women.…”
Section: Discussionmentioning
confidence: 99%